Paediatric reference values for total psoas muscle area. Issue 2 (9th January 2020) - Lurz, Eberhard; Patel, Hiten; Lebovic, Gerald; Quammie, Claudia; Woolfson, Jessica P.; Perez, Manuela; Ricciuto, Amanda; Wales, Paul W.; Kamath, Binita M.; Chavhan, Govind B.; Jüni, Peter; Ng, Vicky L.
Abstract: Background: Sarcopenia, the unintentional loss of skeletal muscle mass, is associated with poor outcomes in adult patient populations. In adults, sarcopenia is often ascertained by cross‐sectional imaging of the psoas muscle area (PMA). Although children with chronic medical illnesses may be at increased risk for muscle loss because of nutritional deficiencies, physical deconditioning, endocrine anomalies, and systemic inflammation, consistent quantitative definitions for sarcopenia in children are lacking. We aimed to generate paediatric reference values for PMA at two intervertebral lumbar levels, L3–4 and L4–5. Methods: In this cross‐sectional study, we analysed abdominal computed tomography scans of consecutive children presenting to the emergency department. Participants were children 1–16 years who required abdominal cross‐sectional imaging after paediatric trauma between January 1, 2005 and December 31, 2015 in a large Canadian quaternary care centre. Children with a documented chronic medical illness or an acute spinal trauma at presentation were excluded. Total PMA (tPMA) at levels L3–4 and L4–5 were measured in square millimetres (mm 2 ) as the sum of left and right PMA. Age‐specific and sex‐specific tPMA percentile curves were modelled using quantile regression. Results: Computed tomography images from 779 children were included. Values of tPMA at L4–5 were significantly larger than at L3–4 at all ages, but their correlation was high for both girls ( r = 0.95) and boys ( r = 0.98). Amongst girls, tPMA 50th percentile values ranged from 365 to 2336 mm 2 at L3–4 and from 447 to 2704 mm 2 for L4–5. Amongst boys, 50th percentile values for tPMA ranged between 394 and 3050 mm 2 at L3–4 and from 498 to 3513 mm 2 at L4–5. Intraclass correlation coefficients were excellent at L3–4 (0.97, 95% CI 0.94 to 0.981) and L4–5 (0.99, 95% CI 0.986 to 0.995). Weight and tPMA were correlated, stratified by sex for boys (L3–4 r = 0.90; L4–5 r = 0.90) and for girls (L3–4 r = 0.87; L4–5 r = 0.87). An online application was subsequently developed to easily calculate age‐specific and sex‐specific z‐scores and percentiles. Conclusions: We provide novel paediatric age‐specific and sex‐specific growth curves for tPMA at intervertebral L3–4 and L4–5 levels for children between the ages of 1‐16 years. Together with an online tool (https://ahrc‐apps.shinyapps.io/sarcopenia/ ), these tPMA curves should serve as a reference enabling earlier identification and targeted intervention of sarcopenia in children with chronic medical conditions.